Evaluation of factors affecting bone mineral density in CF patients through CF registry of Turkey - Soydas, S. S. Akyan; Tugcu, G. D.; Gencoglu, M. Y.; Cinel, G.; Emiralioglu, N.; Yalcin, E.; Dogru, D. (European Respiratory Soc Journals Ltd, 2022)
[Abstract Not Available]
International Congress of the European-Respiratory-Society (ERS) -- SEP 04-06, 2022 -- Barcelona, SPAIN